2008
DOI: 10.1093/sleep/31.5.645
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Usual Sleep Duration with Serum Lipid and Lipoprotein Levels

Abstract: Usual sleep duration is closely associated with serum lipid and lipoprotein levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
165
7
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(189 citation statements)
references
References 37 publications
14
165
7
3
Order By: Relevance
“…The strength of our study was that we included only middle-aged workers in the study population and the HR for events were adjusted for several potential confounding factors. Since there is a U-shaped association between sleep duration and diabetes (20), and an inverse association between sleep duration and hypertension (21-23) and dyslipidemia (24), these traditional cardiovascular risk factors may confound the association between sleep duration and cardiovascular events. However, our study, as well as many previous studies, showed that the increase in cardiovascular and coronary risk was independent of these confounding influences.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of our study was that we included only middle-aged workers in the study population and the HR for events were adjusted for several potential confounding factors. Since there is a U-shaped association between sleep duration and diabetes (20), and an inverse association between sleep duration and hypertension (21-23) and dyslipidemia (24), these traditional cardiovascular risk factors may confound the association between sleep duration and cardiovascular events. However, our study, as well as many previous studies, showed that the increase in cardiovascular and coronary risk was independent of these confounding influences.…”
Section: Discussionmentioning
confidence: 99%
“…An association of self-reported short sleep and/or sleep disruption with MetS has been found in the general population [285][286][287] and shift workers [288,289]. Short sleep duration may increase the risk of incident diabetes [290,291] and stroke [292].…”
Section: The Metabolic Effects Of Sleep Lossmentioning
confidence: 98%
“…In a national study in Japan, sleep duration in adults was closely related with serum lipid and lipoprotein levels (109). Recently, an association between atherogenic dyslipidemia and reduced sleep duration is reported in both U.S. and Hong Kong Chinese adolescents (110,111).…”
Section: Novel Cardiovascular Risk Factors In Adolescents 31 Sleepmentioning
confidence: 98%